Antimicrobial Activity of Zinc Oxide Nanoparticles against bacteria isolated from Goat Wounds - Kadhim, Mahmood Ahmed (Diyala Journal for Veterinary Sciences, 2023)
The aims of this study were to determine the main bacteria species that caused wound infections and to investigate the antibacterial effects of ZnO-NPs against them. Samples were taken from 37 goat wounds. Then wound samples were diagnosed using morphological examination, gram stain examination, and biochemical analysis. Results showed that 21 (56.76%) of the cases were positive, and 16 (43.24%) were negative for bacteria isolation. The main species of bacteria isolated most commonly were Staphylococcus aureus (66.67%), Pseudomonas aeruginosa (23.8%), and Escherichia coli (9.5%). ZnO nanoparticles were tested for antibacterial activity using well diffusion assays at different concentrations (16, 8, 4, and 2 mg/ml). In sensitivity testing of isolates to different concentrations of ZnO NPs, the highest area of inhibition was found in S. aureus (19.67±5.50) mm as compared to P. aeruginosa (22.00±5.29) mm and E. coli (20.67±4.61) mm Mean ±SE. In conclusion, in vitro testing of zinc oxide nanoparticles against bacteria showed that when used at different concentrations, they inhibited bacterial growth at different rates.